THE SATISFACTION USE OF EARLY WARNING SCORE APPLICATION AT PONTIANAK HOSPITAL - Pramana, Yoga; Fradianto, Ikbal; Fauzan, Suhaimi; Maulana, M. Ali; Mita, Mita (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Emergencies are a form of health service in emergency or urgent situations that require immediate action from medical personnel working to overcome potential risks and dangers to life. Various forms of emergency services require nurses in hospitals to save time in the process of providing nursing care. One form of emergency service in hospitals is the Early Warning Score (EWS). The use of technology in developing the Early Warning Score such an application mobile can certainly help in improving the quality of emergency services in hospitals, so it can minimize the severity of patient’s conditions in the emergency phase.Method: The method in this research is quantitative descriptive research, in this case the Android-based mobile Early Warning Score application. This research was conducted to measure the level of user satisfaction where there are 3 dimensions in measuring the level of satisfaction with application use: quality of application information, quality of application use, and impact of application use.Results: The results of the research show that the satisfaction level of the Early Warning Score mobile application at Pontianak Hospital obtained a total score of 419 or 50,60% is satisfied, and very satisfied with total score of 217 or 26.21%.Conclusion: The Early Warning Score mobile application is suitable for use by nursing staff as a medium for improving excellent nursing services.